KONTRIBUSI POWER OTOT TUNGKAI DAN FLEKSIBILITAS TERHADAP KETERAMPILAN SMASH SEPAK TAKRAW DI CLUB RANGSANG KABUPATEN PULAU MERANTI - Azizan Hakim; Zainur Zainur; Fekie Adila; Ittaqwa Ittaqwa; Muhammad Iman Ramatullah (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
Some problem in this research possession of the ball always fails when receiving service from the opposing team, due to a lack of eye-foot coordination, which should be controlled but the ball is not aimed. In addition, the maximum smash power has not yet been reached. This research aims to investigate whether there is a contribution between leg muscle strength and flexibility on smashing skills. This type of research uses correlational. The sampling technique was targeted sampling, which was 10 people from the exciting sepak takraw club. The instruments used in this research were vertical jumping, sitting and reaching, and smashing skills. Based on data analysis and discussion of the calculation results, it is obtained that the multiple correlation coefficient (R-test) is obtained by R-count = 0,962, while Rtable is obtained at 0.789, so Rcount > Rtable, which means that there is a concurrent relationship. Thus, it can be concluded that the strength and flexibility of the leg muscles together contributed significantly to the takraw smashing skills at Rangsang Kepulauan Meranti club.